Pandemic Politics Through Social Media: A Study of India - Aijaz Ahmad Mir (Journal of Political Studies, 2022)
This paper discusses the use of social media by the ruling party BJP and its opposition, especially Congress, during the pandemic in India. The party at the centre has used social media, especially for two reasons; firstly, the BJP leveraged social media to promote the image of India as a “responsible sovereign” at the global level during the COVID-19 pandemic. The Indian government, under the leadership of Narendra Modi, has exported drugs and medicines to different countries during the first wave of the COVID-19 pandemic. The party has extensively used social media platforms, especially Twitter, to engage with global leaders during the pandemic. Secondly, the party and its right-wing supporters have used social media to highlight the achievements of Modi’s government at the domestic level. The ruling party has used a “free vaccination campaign” for its political gains, and Narendra Modi was portrayed as the “savior” of the Indian people during the pandemic. The BJP and its supporters have also employed social media to target Muslim minorities during the pandemic. This paper also discusses the opposition parties' use of social media, especially Congress, during the pandemic phase in India. The opposition parties have mainly used social media to target and expose the weaknesses of Modi’s government in handling the pandemic in India. This paper analyses the different themes, such as the ruling party’s use of social media to promote its image both at the global and at domestic level, targeting of Muslims for spreading coronavirus, role of opposition parties, internal disputes, international status-seeking, and vaccine diplomacy. To fulfill the requirements of this study, both primary and secondary data collection methods were used.